(untitled) (Superficies y Vacío, 2015)
We report the preparation of zinc peroxide nanoparticles (ZnO2 NPs) by the laser ablation of solid in liquids technique. Experiments were performed by using the fundamental wavelength (1064 nm) of a pulsed nanosecond Nd:YAG laser operated at a repetition rate of 15 Hz. A Zn disk (99.99 % purity) were the target and 10 ml of 30% H2O2 solution was used as liquid medium. The per pulse laser fluence was varied. In all the experiments the ablation time was 10 min. The samples were characterized by Raman microspectroscopy, Calorimetry and TEM. Results show that ZnO2 NPs were successfully obtained by this method of preparation.